2018
DOI: 10.1007/s00894-018-3720-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of a DMSO/water mixture using the AMBER force field

Abstract: Due to its protective properties of biological samples at low temperatures and under desiccation, dimethyl sulfoxide (DMSO) in aqueous solutions has been studied widely by many experimental approaches and molecular dynamics (MD) simulations. In the case of the latter, AMBER is among the most commonly used force fields for simulations of biomolecular systems; however, the parameters for DMSO published by Fox and Kollman in 1998 have only been tested for pure liquid DMSO. We have conducted an MD simulation study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Many experimental and theoretical investigations have been made into the structure of liquid solutions of DMSO, particularly around the 1:2 composition where the meltingpoint depression is greatest (e.g. Soper & Luzar, 1992;Vishnyakov et al, 2001;Bordallo et al, 2004;McLain et al, 2007;Wallace et al, 2015;Oh et al, 2017;Stachura et al, 2018;Wei et al, 2018;Yang et al, 2020). The prevailing interpretation of DMSO-water liquid data is in terms of 1:3 and 1:2 DMSOwater clusters and possible association into DMSO-(water) n -DMSO chains (Zhang et al, 2009;Idrissi et al, 2015;Verstakov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and theoretical investigations have been made into the structure of liquid solutions of DMSO, particularly around the 1:2 composition where the meltingpoint depression is greatest (e.g. Soper & Luzar, 1992;Vishnyakov et al, 2001;Bordallo et al, 2004;McLain et al, 2007;Wallace et al, 2015;Oh et al, 2017;Stachura et al, 2018;Wei et al, 2018;Yang et al, 2020). The prevailing interpretation of DMSO-water liquid data is in terms of 1:3 and 1:2 DMSOwater clusters and possible association into DMSO-(water) n -DMSO chains (Zhang et al, 2009;Idrissi et al, 2015;Verstakov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations 25,24 have shown that there is a 20% increase of binding energy of H 2 with SiCNTs compared to pure CNTs. Computational modeling has already been successfully utilized to investigate a wide range of biologically significant phenomena such as the behavior of organic solvents in water, 26,27 the insulin signaling system, 28 β amyloid protein interaction with the membrane, 29 the antioxidant properties of nanostructures, 30,31 or the interaction of human immunodeficiency virus-binding peptide with the biomembrane. 32 Needless to say that by taking into account the available computational power and the level of the complexity of the systems composed of the heterogeneous nanotube and the phospholipid bilayer, only the classical molecular dynamics (MD) technique can be applied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The solvent was described with the TIP3P water model . With respect to the AMBER parameter set for DMSO, we have recently shown that it faithfully reproduces a number of important experimental properties of DMSO in TIP3P water …”
Section: Methodsmentioning
confidence: 99%
“…While this methodology and these model systems are not especially unique, recent force-field advancements and the ability to explore longer simulation timescales gave us some confidence that we could elucidate some of the inconsistencies observed across earlier studies. For instance, we have previously demonstrated that the AMBER parameter set for DMSO faithfully reproduces a number of important experimental properties of DMSO in water . In terms of lipid force fields, Lipid14 was developed with updated Lennard-Jones and torsion parameters as well as refined partial charges compared with its predecessor Lipid11 in order to better reproduce a wide range of experimentally characterized membrane properties for several lipid types including DOPC .…”
Section: Introductionmentioning
confidence: 99%